Implementing Co-Regulated Feeding with Mothers of Preterm Infants. Issue 4 (July 2016) - Thoyre, Suzanne M.; Hubbard, Carol; Park, Jinhee; Pridham, Karen; McKechnie, Anne
Abstract: Purpose: The purpose of this study is to describe implementation of the Co-Regulated Feeding Intervention (CoReg), when provided by mothers and guided by intervention nurses trained in methods of guided participation (GP). Co-regulated feeding intervention aims to prevent stress during feeding and ease the challenge very preterm (VP) infants experience coordinating breathing and swallowing during the early months. Guided participation is a participatory learning method to guide the complex learning required for mothers. Study Design and Methods: Sixteen mothers of 17 VP infants participated. Each mother received a median of five intervention sessions during the infant's transition to oral feeding. Intervention field notes, audio recordings of the sessions, and video recordings of the nurse-guided feedings were reviewed, organized, and content analyzed to evaluate implementation. Results: The co-regulated feeding intervention was well received by mothers; enrollment, participation, and retention rates were high. Most mothers chose to spread out the intervention sessions across the transition period. Scheduling sessions was the greatest barrier. Mothers had competing demands and infant readiness to eat could not be predicted. The top five issues identified as needing attention by the mother or nurse included reading cues, coregulating breathing, providing motoric stability, regulating milk flow, and providing rest periods. Main GP strategies included joint attention with the mother to the dyad's feeding challenges, auditory assessment of breathing and swallowing, and reflection with planning for future feedings using video playback. Clinical Implications: Nurse presence while mothers feed affords rich opportunities to guide coregulated, cue-based feeding. Co-regulated feeding intervention would be enhanced if mothers are guided by the bedside nurse. Abstract : Co-Regulated Feeding is used to prevent stress during feeding and ease the challenges very preterm infants experience coordinating breathing and swallowing during the early months. This study evaluates implementation of co-regulated feeding. Presence of the nurse while mothers feed their very preterm infant offers an opportunity to guide mothers in co-regulated, cue-based feeding.